Students' Perceptions of Grammarly Application Feedback on Writing Skill at SMAN 4 Palangka Raya - Erisyerico, Mimo Lalito; Perdana, Indra; Karani, Elanneri (PROJECT (Professional Journal of English Education), 2025)
Grammarly is an online tool that helps users improve their writing by correcting errors in grammar, vocabulary, and mechanics. With its growing use among students, it is important to understand their perceptions of the tool. This research investigates the perceptions of SMAN 4 Palangka Raya students regarding Grammarly's feedback on their writing skill during the 2024–2025 academic year. Using a descriptive quantitative design, a survey was distributed to 91 students who regularly used Grammarly. The questionnaire gathered data on students' perceptions of Grammarly's feedback features, quality and impact, and overall usage. Analysis was conducted using frequency distributions, percentages, and mean scores in Microsoft Excel. The results show that students have a positive perception of Grammarly, with a mean score of 4.19, highlighting its effectiveness in improving grammar, vocabulary, and mechanics. Students value its ability to identify errors, suggest vocabulary, and correct spelling, punctuation, and capitalization. Grammarly's feedback not only enhances writing quality but also boosts confidence and motivation. The tool's accessibility and user-friendly interface, even in the free version, further reinforce its positive perception. However, individual factors such as prior writing ability, learning preferences, and technical issues influenced how students perceived its effectiveness.